2020
DOI: 10.1021/acs.joc.0c00341
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Bromoboration of Acetylene with Boron Tribromide: Preparation and Cross-Coupling Reactions of (Z)-Bromovinylboronates

Abstract: The mechanism of acetylene bromoboration in neat boron tribromide was studied carefully by means of experiment and theory. Besides the syn-addition mechanism through a four-center transition state, radical and polar anti-addition mechanisms are postulated, both triggered by HBr, which is evidenced also to take part in the Z/E isomerization of the product. The proposed mechanism is well supported by ab initio calculations at the MP2/6-31+G* level with Ahlrichs' SVP all-electron basis for Br. Implicit solvation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Despite the theoretical drawbacks described, the radical mechanisms proposed in this work are consistent with available experimental data [ 9 ]. They thus offer a novel point of view on the mechanism of bromoboration and haloboration reactions and, in a wider context, on the isomerizations of substituted alkenes in general.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Despite the theoretical drawbacks described, the radical mechanisms proposed in this work are consistent with available experimental data [ 9 ]. They thus offer a novel point of view on the mechanism of bromoboration and haloboration reactions and, in a wider context, on the isomerizations of substituted alkenes in general.…”
Section: Discussionsupporting
confidence: 85%
“…A 2013 joint experimental and theoretical study by Lawson et al reported the first successful haloboration/esterification of internal alkynes [ 8 ]. Finally, inspired by the previous work by Mazal and Vaultier [ 4 ], we concentrated on the stereoselective bromoboration of acetylene with boron tribromide as a route to ( Z )-Bromovinylboronates, with mechanistic studies supported by ab initio calculations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations